Study on the factors which influence youth knowledge in IM4U program at Taman Malinja, Bukit Baru, Melaka / Muhammad Farhan Muhamad and Nuzrulizwan Mohd Salehan - Muhamad, Muhammad Farhan; Mohd Salehan, Nuzrulizwan (Faculty of Administrative Science and Policy Studies, 2013)
Youth is a person within or age between 18 years old to 40 years old that usually has the intention or behavior in trying to do something or having the desire in trying something new and different with other. It is because at this age, they might have the rebellious behavior inside them. Most of the factor that may shape their attitude and behavior by doing a program that can refresh their mind and make them think critically on the basic need in continue to live in their daily life. According to Kenedy (1997), youth also define as the appearance, freshness, vigor, and spirit, characteristic of one who is young. Furthermore, Doortja, Upeka & Ebrima (2004), youth participation is valued as the human right in which both youth people and adult and need to embrace change and be ready to standby and support each other for organizational and mutual benefits. They said, it must be underpinned by democratic values and principles of non-discrimination and equity. In Malaysia the Ministry of Youth and Sports (MOYS), mainly function as contributing to the development of youth policy, through its position as chair of the National Youth Consultative Council (NYCC) and serve as the policies key implementation body. The Youth Division consist of many department such as youth economic development department, youth NGO`s Development department, Rakan Muda (youth partners) program and also department of skill and training institute.